Travels and Identities : Elizabeth and Adam Shortt in Europe, 1911 - Shortt, Adam, 1859-1931; Smith, Elizabeth, 1859-1949; Dembski, Peter E. Paul, 1938- (Book collections on Project MUSE., 2017)
Diaries and letters of Adam and Elizabeth Shortt from their 1911 voyage from Canada to England, their extended visit there and later trips to the continent. Introduction and conclusion analyze the various identities of the travelers.